PERFORMANCE EVALUATION OF H.264/AVC DEBLOCKING FILTER FOR 720P HIGH DEFINITION VIDEO - Raja, G. (The Nucleus, 2011)
High definition Video (HDV) is increasingly becoming common feature in video display devices as it provides superior level of details in comparison to standard video. Latest video compression standard, H.264/AVC can be used for storage and efficient transmission over network. However, blocking artifacts are introduced due to loss of correlation between blocks during compression process. H.264/AVC employs deblocking filter to suppress these blocking artifacts. This paper provides performance evaluation of H.264/AVC deblocking filter for 720p high definition video. Various simulations by using different 720p video sequences are conducted to check the efficiency of H.264/AVC deblocking filter. Simulation results show that H.264/AVC deblocking filter can enhance the perceptual quality of 720p video by suppressing the blocking artifacts.